Hybrid Power Generating System Using Solar PV and Vertical Axis Wind Turbine with Automatic Street Light Control In Roadways - M. Senthilkumar, Ambrish V, Harshini A, Abilash C, Haricharann DV (International Journal of Advanced Science and Technology, 2020)
Renewable energy sources generated from solar, wind, biomass, hydropower, geothermal and ocean resources are considered as a technological option for generating clean energy. But the energy generated from solar and wind is much less than the production by fossil fuels, however, electricity generation by utilizing PV cells and wind turbine increased rapidly in recent years. In this invention we have used a solar tracking system which is monitored and controlled by LDRs and ATmega328P controller coupled with a vertical axis wind turbine. Even in the absence of any of these systems, electricity can be harvested. The entire system will be placed at the divider of the highway roads. The single axis solar tracker will be placed at the top and it tracks the maximum intensity throughout the day and gives its output to a battery. The VAWT on the other hand will use the wind energy produced due to the movement of vehicles on the either sides of the road and produces its equivalent power in DC (dynamo is used). The output is stored in the same battery. Using another controller (ATmega328P) and another LDR, automation of street light is done. When the value of the resistance of the LDR goes below a threshold value, the street lights are triggered to get energised by drawing the power stored in the battery through a relay. An inverter is used after the battery. The main idea of this automation is use the power efficiently only during the night times.